What makes people accept carbon capture and utilization products? Exploring requirements of use in the German population - Haverkämper, Imke; Wilkowska, Wiktoria; Ziefle, Martina (Frontiers in Energy Research, 2023)
Carbon Capture and Utilization (CCU) is often referred to as an important cornerstone in the context of counteracting climate change. It aims to capture CO2 from various sources and to store it in valuable products more or less permanently. While the environmental impact of this technology has already received much scientific attention, this work takes a social science perspective on the matter. Using an empirical mixed-methods approach consisting of an exploratory focus group study (N = 13) and a validating quantitative questionnaire study (N = 198), public perceptions and acceptance of CCU were assessed in Germany by identifying motivators, barriers, and usage requirements. As CCU products, clothing, cosmetics, and food packaging were under study. Potential cost savings from shortened supply chains or manufacturing steps were the biggest motivator for using CCU. However, environmental impacts resulting from the degradation and reuse of CO2 were also recognized and the conservation of fossil resources was also acknowledged. The biggest barrier, in contrast, was the concern about possible manipulation of consumers through marketing. Participants feared that CCU would be publicly portrayed as better than it actually is. In addition, a high energy input in the production of CCU products was expected and doubts were expressed about the longevity of the positive environmental impacts of CCU. General acceptance within the sample was quite high, however, the level of CCU awareness was rather low. Our results show a considerable lack of public knowledge about and information regarding the environmental impact of CCU, among other factors, despite this very topic garnering plenty of scientific attention. A need for publicly accessible information materials uniquely tailored toward potential consumer target groups was revealed.